Efficacy of Trimebutine Maleate (Trimedat®) in the Treatment of Patients with Functional Dyspepsia: Results of the “TREND” Observational Study - S. S. Kardasheva; I. M. Kartavenko; N. B. Maksimova; E. Yu. Yurieva; I. R. Popova; Ch. S. Pavlov; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. This research is aimed at investigating the experience of applying trimebutine maleate in the daily practice of physicians managing patients with functional dyspepsia syndrome (FDS).Materials and methods. The study included 100 patients diagnosed with FDS. The patients were asked to complete a 7 × 7 and SF36 questionnaires before and on the 7th, 14th, 28th days of treatment. The treatment was performed using trimebutine (Trimedat®) in a standard dosage of 200 mg × 3 times a day for 28 days.Results. In the group under study, 45 (45 %), 3 (3 %) and 52 (52 %) patients suffered from epigastric pain syndrome (EPS), postprandial distress syndrome (PPDS) and a combination of both syndromes, respectively. The combination of FDS with gastroesophageal reflux disease (GERD) was noted in 15 patients (15 %). Irritable bowel syndrome (IBS) was present in 21 cases (21 %). Trimebutine maleate (Trimedat®) has been proven effective in all FDS forms, such as EPS, PPDS and their combination. In the course of treatment, the average score of the patients’ physical and mental health increased from 48.02 ± 5.62 to 52.97 ± 4.17 points (p < 0.0001), and from 48.48 ± 10.83 up to 51.79 ± 8.51 points (p < 0.0001), respectively.Conclusion. The main clinical forms of functional dyspepsia syndrome (EPS and PPDS) are frequently manifested in combination either with each other (52 %), or with IBS (21 %) and GERD (15 %). The use of trimebutine in the treatment of patients with FDS is shown to result in a decrease in the severity of its main symptoms and a reliable increase in the quality of patients’ life.